Negative effects of pesticides under global warming can be counteracted by a higher degradation rate and thermal adaptation. Issue 6 (2nd May 2017) - Op de Beeck, Lin; Verheyen, Julie; Olsen, Kent; Stoks, Robby
Summary: An alarming finding for biodiversity is that global warming and pesticides often interact synergistically. Yet, this synergism may not capture the full picture because two counteracting processes may reduce the higher impact of pesticides under warming: higher pesticide degradation in the environment and thermal adaptation of populations. We tested for the effects of warming and multiple pulses of the insecticide chlorpyrifos on life history and fitness‐related physiological traits in the damselfly Ischnura elegans . To assess whether thermal adaptation is able to mitigate the impact of the pesticide under future warming, we exposed replicated populations from a colder, high latitude and from a warmer, low latitude in a common garden rearing experiment at 20 and 24 °C (the respective mean summer water temperatures at both latitudes). At the higher temperature pesticide degradation was higher, leading to less accumulation after multiple pulses compared to the lower temperature. Accordingly, the pesticide caused less mortality and less oxidative damage at the higher temperature. This contradicts the general belief (based on studies that kept pesticide concentrations constant) of a higher impact of pesticides under warming. Furthermore, the reduction of the impact of the pesticide at the higher temperature was more pronounced in the warm‐adapted low‐latitude populations, indicating a counteracting role of thermal adaptation. Policy implications . Our findings provide proof‐of‐principle for two key insights that will allow improving ecological risk assessment of pesticides under global warming: (i) higher pesticide degradation in the environment under warming may temper the impact of multiple pesticide pulses; (ii) gradual thermal evolution may further reduce the impact of pesticides at high latitudes under global warming. This knowledge can be very important for policy makers to arrive at a more realistic forecasting of the impacts of chemical pollution and climate change interactions on organisms. Abstract : Our findings provide proof‐of‐principle for two key insights that will allow improving ecological risk assessment of pesticides under global warming: (i) higher pesticide degradation in the environment under warming may temper the impact of multiple pesticide pulses; (ii) gradual thermal evolution may further reduce the impact of pesticides at high latitudes under global warming. This knowledge can be very important for policy makers to arrive at a more realistic forecasting of the impacts of chemical pollution and climate change interactions on organisms.